Meta-analisis model inquiry based learning untuk pembelajaran IPA dan fisika pada abad 21 - Tri Septiani; Novelia Prima; Fitri Nisak (Universitas Negeri Padang, 2019)
Significant influence of the 21st century provides a change in education in Indonesia. The 21st century requires everyone to have a variety of skills to be able to compete in the face of the changing times. The government changed the curriculum from KTSP to 2013 curriculum. The 2013 curriculum suggested appropriate learning models used for science and physics learning, one of which was the Inquiry Based Learning (IBL) model. This study aims to analyze the IBL model in learning physics and science. This research method is a meta-analysis with a sample of 10 articles in national journals. The result of this meta-analysis research is that the IBL model can improve student learning outcomes. Media and teaching materials used to support the implementation of the IBL model are virtual laboratories and student worksheets. The dominant material used in the IBL research model is temperature and heat. Most of the research conducted is experimental research, some research development and classroom action research. Therefore, the IBL model is very good to use if the media and teaching materials are used are virtual laboratories and student worksheet.